Application For Dissolution of Limited Liability Company Submitted By The Attorney In The Public Interest - Putri, Ayudita Supriyanto; Sjafi’i, Imam Rahmat (International Journal of Business, Law, and Education, 2024)
This study is motivated by the absence of limitations on the meaning of the phrase public interest in Article 146 paragraph (1) letter a of Law Number 40 of 2007 concerning Limited Liability Companies. Therefore, it leads to a blurring of norms. Furthermore, the objectives of this study are (1) to understand and analyze the authority of the Prosecutor's Office in submitting a request for dissolution of a Limited Liability Company to the District Court; and (2) to understand and analyze the limitations of the meaning of the phrase public interest as intended in Article 146 paragraph (1) letter a of Law Number 40 of 2007 concerning Limited Liability Companies based on Balikpapan District Court Decision Number 457/Pdt.P/2019/PN Bpp. This study was normative juridical research by using a statutory approach and a case approach. Legal materials were analyzed by using prescriptive analysis methods. The study shows that the authority of the Prosecutor's Office to dissolve a company is regulated in Article 146 paragraph (1) letter a UUPT where the Prosecutor's Office is given the authority in order to dissolve a company which is deemed to violate the public interest. However, the criteria for violations of the public interest are not explained. Therefore, there is no clear definition of the meaning of this public interest phrase. In addition, the provisions and meaning of public interest are now very flexible in accordance with relevant regulations. Keywords: Prosecutor’s Application, Limited Liability Company, Public Interest